Efficient Numerical Methods for Dynamic Simulation of Fixed-bed Reactors - Rosbo, Joachim Weel; Jensen, Anker D.; Jørgensen, John Bagterp; Huusom, Jakob K. (Computer Aided Chemical Engineering, 2024)
The intermittent nature of renewable energies requires Power-to-X (P2X) plants to operate flexibly in contrast to traditional stable operation with fossil feedstocks. This emphasises the need for accurate and efficient dynamic models of P2X plants. In this paper, we study a partial differential algebraic equations (PDAEs) model for a fixed-bed gas phase reactor. The model is discretized in space by the finite volume method (FVM). The dispersion term from back-mixing in the bed is approximated by numerical diffusion by using an appropriate number of discretization cells. Five different numerical implementations of the Euler step are investigated for solving in time: One traditional explicit scheme and four implicit formulations. The performance of the numerical schemes is tested by solving the response of the bed to a step change in the inlet temperature. The most efficient implicit method is an order of magnitude faster than the traditional explicit method, while the slowest implicit method is an order of magnitude slower.